Crystal Initiation Structures in Developing Enamel: Possible Implications for Caries Dissolution of Enamel Crystals - Robinson, Colin; Connell, Simon D. (Frontiers in Physiology, 2017)
Investigations of developing enamel crystals using Atomic and Chemical Force Microscopy (AFM, CFM) have revealed a subunit structure. Subunits were seen in height images as collinear swellings about 30 nM in diameter on crystal surfaces. In friction mode they were visible as positive regions. These were similar in size (30-50nM) to collinear spherical structures, presumably mineral matrix complexes, seen in developing enamel using a freeze fracturing/freeze etching procedure. More detailed AFM studies on mature enamel suggested that the 30-50nM structures were composed of smaller units, 10-15nM in diameter. These were clustered in hexagonal or perhaps a spiral arrangement. It was suggested that these could be the imprints of initiation sites for mineral precipitation. The investigation aimed at examining original freeze etched images at high resolution to see if the smaller subunits observed using AFM in mature enamel were also present in developing enamel i.e. before loss of the organic matrix. The method used was freeze etching. Briefly samples of developing rat enamel were rapidly frozen, fractured under vacuum and ice sublimed from the fractured surface. The fractured surface was shadowed with platinum or gold and the metal replica subjected to high resolution TEM. For AFM studies high-resolution tapping mode imaging of human mature enamel sections was performed in air under ambient conditions at a point midway between the cusp and the cervical margin. Both AFM and freeze etch studies showed structures 30-50nM in diameter. AFM indicated that these may be clusters of somewhat smaller structures 10-15nM maybe hexagonally or spirally arranged. High resolution freeze etching images of very early enamel showed 30-50nM spherical structures in a disordered arrangement. No smaller units at 10-15nM were clearly seen. However, when linear arrangements of 30-50nM units were visible the picture was more complex but also smaller units including 10-15 nM units could be observed. CONCLUSIONS Structures 10-15nM in diameter were detected in developing enamel. While the appearance was complex, these were most evident when the 30-5nM structures were in linear arrays. Formation of linear arrays of subunits may be associated with the development of mineral initiation sites and attendant processing of matrix proteins.